Making matters worse by trying to make them better? Exploring vicious circles of decision in hybrid partnerships. Issue 9 (September 2019) - Ungureanu, Paula; Bertolotti, Fabiola; Mattarelli, Elisa; Bellesia, Francesca
Our research is concerned with how and why vicious circles of decision occur in hybrid partnerships. The literature reports three types of decision dysfunctions that can alter the trajectory of multi-stakeholder collaborations: escalation of commitment, procrastination and indecision. While previous studies focused on one dysfunction at a time, we inquire about cases in which dysfunctions coexist and interact in the same partnership. Employing multiple sources of qualitative data, we conducted a longitudinal field study in a cross-sector partnership that co-created and managed a science park. We offer an in-depth account of 'vicious circles of decision' in which partners' attempts to solve a dysfunction paradoxically led to the accumulation of additional dysfunctions. We explain that the process is more likely to happen when solutions are (1) conditioned by the very risk–opportunity tensions they try to solve and (2) inscribed in material artefacts for greater visibility. As well as augmenting the literature on hybrid partnerships, we contribute to the debate in organization studies about the evolution of collaborations within frames of concurrent risk–opportunity tensions and theorize about the role of materiality in such processes.